Aubrieta necmi-aksoyi (Brassicaceae), a new species from Turkey and a key to the species of Aubrieta - Tunçkol, Bilge; Özkan, Neval Güneş; Al-Shehbaz, Ihsan A. (Phytotaxa, 2022)
Aubrieta necmi-aksoyi is described as a new Turkish species endemic to Bolu Province. Its relationships to the closely related A. alshehbazii and A. ekimii are discussed. A detailed genereic description and a key to all Turkish species of Aubrieta are presented.